OPTIMASI RANTAI PASOK AGRIBISNIS PADA UMKM: PEMANFAATAN TEKNOLOGI DIGITAL - Nugra Irianta Denashurya (Jurnal Pertanian Agros, 2026)
The agricultural sector plays a crucial role in developing economies such as Indonesia, particularly in regions like West Kalimantan where it supports a large share of the population. However, Micro, Small, and Medium Enterprises (MSMEs) face persistent supply chain challenges, including inefficiencies, high operational costs, and limited market access. This study aims to examine the role of digital technologies in optimizing agribusiness supply chains among MSMEs in West Kalimantan, grounded in the Resource-Based View (RBV) and Dynamic Capabilities theory. This research employs a mixed-methods approach, combining quantitative data from a survey of 100 MSMEs and qualitative insights from in-depth interviews with 20 selected participants. Quantitative data were analyzed using regression analysis, while qualitative data were examined through thematic analysis. The findings indicate that digital technology adoption significantly improves supply chain efficiency, product traceability, and market access. However, adoption remains limited due to barriers such as inadequate infrastructure, high implementation costs, and low digital literacy. The study highlights the importance of external support, including government policies and public–private partnerships, to enhance digital adoption.This research provides practical and theoretical insights into the strategic role of digital technologies in strengthening MSME competitiveness and supporting sustainable rural development.